An integrated strength-carbon emissions-total cost model for silica fume concrete - Li-Yi Meng; Yi-Sheng Wang; Feng Sun; Runsheng Lin; Xiao-Yong Wang (Case Studies in Construction Materials)
Silica fume (SF) is widely used as an additive to produce high-performance concrete. Previous models for evaluating the sustainable performance of silica fume concrete lacked systematicity and were not convenient for engineering applications. The objective of this study was to propose a comprehensive hydration-strength-carbon emission-total cost model for silica fume (SF) concrete. This paper proposes an integrated hydration-strength-carbon emissions-total cost model for SF concrete. First, based on the hydration model, the reaction levels of SF and the hydration degree of cement were calculated. Through linear regression, a compressive strength prediction formula for SF concrete with varying water-cementitious material mass ratios (0.79–0.45), different SF contents (0–20 %), and curing ages (1–365 days) was developed. The correlation coefficient between the test results and the predicted results was 0.979, and the root mean square error was 4.395 MPa. sondly, based on the mix ratio, the material cost and CO₂ emissions of concrete per 1 MPa strength were calculated. It was found that with the increase in SF content, the material cost per 1 MPa strength increased, while the CO₂ emissions per 1 MPa strength decreased. The CO₂ emissions were converted into costs using the carbon price, and the total cost was calculated as the sum of the material cost and the CO₂ emission cost. Parameter analysis revealed that using SF increased the overall cost at the current carbon price. If the carbon price were to increase by 2, 3, or 4 times, the overall cost trend would remain unchanged. As the silica fume content increases, the energy consumption per unit strength of silica fume concrete increases, and the solid waste generation per unit strength of silica fume concrete decreases.